1999
DOI: 10.1038/sj.bjp.0702471
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of exercise capacity of rats with chronic heart failure by long‐term treatment with trandolapril

Abstract: 1 The eects of long-term treatment with trandolapril, an angiotensin I-converting enzyme inhibitor, on exercise capacity of rats with chronic heart failure (CHF) following coronary artery ligation were examined. CHF was developed by 8 weeks after the coronary artery ligation. 2 The running time of rats with CHF in the treadmill test was shortened to approximately 65% of that of sham-operated rats (16.3+1.2 vs 25.1+1.6 min, n=7; P50.05). ATP, creatine phosphate (CP), and lactate contents of the gracilis muscle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 31 publications
2
12
0
Order By: Relevance
“…Whether the pharmacological inhibition of ACE affects the mitochondrial function has been previously studied. Prolonged ACE inhibition completely prevented the decreased skeletal muscle oxidative capacity expected in patients with chronic heart failure (10) and in rats with heart failure secondary to myocardial infarction (32,35). However, this protective effect of ACE inhibition remains controversial, and perindopril administration failed to restore muscle oxidative capacity and mitochondrial function in a rat model of heart failure induced by aortic stenosis (16) or in a rat model of type I diabetes (22).…”
Section: Discussionmentioning
confidence: 99%
“…Whether the pharmacological inhibition of ACE affects the mitochondrial function has been previously studied. Prolonged ACE inhibition completely prevented the decreased skeletal muscle oxidative capacity expected in patients with chronic heart failure (10) and in rats with heart failure secondary to myocardial infarction (32,35). However, this protective effect of ACE inhibition remains controversial, and perindopril administration failed to restore muscle oxidative capacity and mitochondrial function in a rat model of heart failure induced by aortic stenosis (16) or in a rat model of type I diabetes (22).…”
Section: Discussionmentioning
confidence: 99%
“…Left anterior descending coronary artery ligation was used to produce myocardial infarction and consequent HF in rats, as this model has been shown to have significant reductions in exercise capacity (Yamaguchi et al, 1999;Pfeifer et al, 2001;Koh et al, 2003). Alterations in skeletal muscle Ca 21 sensitivity and handling have also been noted with heart failure (Ward et al, 2003;Kho et al, 2012b), and pharmacological calcium sensitizers have previously been shown to increase calcium sensitivity in diaphragms from heart failure rats (van Hees et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The animals were submitted to physical exercise on the treadmill (Yamaguchi et al, 1999), with the exception of an extra group, which did not exercise (control without stress). The fatigue protocol consisted of a 3 min run to warm-up at 4 m/min, 3 min at 8 m/min, 9 min at 14 m/min, 5 min at 20 m/min, 5 min at 26 m/min and finally 5 min at 32 m/min.…”
Section: Animalsmentioning
confidence: 99%